Implikasi Kewenangan Mendagri Dalam Membatalkan Perda Pasca Putusan Mahkamah Konstitusi Republik Indonesia - Karman Jaya; Firman Tongke (Ikatan Ahli Informatika Indonesia, 2023)
The basic problem of this research is how judges consider and the legal implications in decisions regarding the revocation of the Minister of Home Affairs' authority in canceling Regency/City Regional Regulations and this type of research uses a type of library research which is also called library research, namely research that emphasizes the source of information from legal books, journals and literature related or relevant to the object of study. The data sources for this research come from primary legal materials. This research comes from reading literature, including reading books, historical manuscripts, mass media reading sources and other reading sources. The results of this research show that the review of statutory regulations under the law is within the power of the Judiciary. This can be seen constitutionally that the Court Agung has the authority to review statutory regulations under the Law against this Law as a form of implementation of the mandate of Law Number 48 of 2009 concerning Judicial Power which replaces Law Number 4 of 2004 in Article 20 paragraph (2) stated, “The Supreme Court has the authority to: b. test the statutory regulations under the law against the law”. The existence of judicial review in a rule of law state is one of the conditions for the establishment of the rule of law itself, as stated in Article 1 paragraph (3) of the 1945 Constitution.